Improving children's learning: Effective teaching in the primary school - Dean, Joan (Educational management series, 2000)
How can teachers improve what they do in the primary classroom? Which teaching methods will help you and your pupils to perform effectively? These are the questions that every teacher will be asking him or herself in today's climate of targets and tables. Much research over recent years has focused on the role of the teacher and how effective classroom practice is achieved. The book discusses many areas of topical importance including: teaching methods motivating learners and matching work to children how to structure children's learning classroom control and organisation teaching literacy teaching children with special education needs working with parents. It also looks at the increasing role of the teacher as a researcher and how colloborative practices are providing a way for teaches to appraise both their own progress and that of their colleagues. This book should be of particular interest to the classroom teacher who is looking for ways to develop his or her teaching but has limited time to explore the research. It sets out to translate the findings of research into practical terms which teachers can easily use.